1998
DOI: 10.1016/s0741-5214(98)70091-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoleak after aortic stent graft repair: Diagnosis by color duplex ultrasound scan versus computed tomography scan

Abstract: Although most of the CDU studies were technically suboptimal, the CDUs reliably identified endoleaks with an excellent sensitivity and a negative predictive value as compared with CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 16 publications
4
112
0
1
Order By: Relevance
“…To our knowledge no study has compared the value of CT angiography as an alternative to DU in the follow-up of popliteal artery diseases. However, the majority of reports on DU performance to detect endoleaks after endovascular repair of abdominal aortic aneurysm [26][27][28][29][30][31] found inferior sensitivity and specificity compared to CT angiography. Nevertheless, contrast agents (Levovist) seem to increase the sensitivity of this color-flow DU, but with the risk of more false-positive results [32].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge no study has compared the value of CT angiography as an alternative to DU in the follow-up of popliteal artery diseases. However, the majority of reports on DU performance to detect endoleaks after endovascular repair of abdominal aortic aneurysm [26][27][28][29][30][31] found inferior sensitivity and specificity compared to CT angiography. Nevertheless, contrast agents (Levovist) seem to increase the sensitivity of this color-flow DU, but with the risk of more false-positive results [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is limited by the patient's body habitus, overlying bowel gas, technician's skill, and inconsistent ability to image the proximal infrarenal aorta. [2][3][4][5][6] A CT scan does not image flow directly. High attenuation structures, such as calcium or residual radiopaque contrast, may simulate abnormal blood flow into extravascular spaces, as seen with endoleaks.…”
Section: Discussionmentioning
confidence: 99%
“…The two modalities are complementary, and when performed in an accredited vascular laboratory by experienced technologists, duplex ultrasound is a highly sensitive and specific method of detecting extrastent flows. [2][3][4][5][6] We present a case of extrastent contrast without evidence of active extravasation seen on spiral CT at 40 hours postoperatively.…”
mentioning
confidence: 88%
“…In addition, satisfactory images cannot be obtained in some patients because of technical inability (ie, obesity or excessive intestinal gas). A review of the CDU studies from multiple centers for the EnACT stent-graft trial (Sato et al, 1998), revealed that most of the studies were suboptimal in the evaluation for endoleaks. Although approximately 90% of the studies were technically possible, as indicated with satisfactory Bmode images, complete evaluation for endoleaks as outlined in the methods described was obtained in only 19% of the studies.…”
Section: Color Duplex Ultrasound Limitationsmentioning
confidence: 99%